Strategies for Discovery of Small Molecule Radiation Protectors and Radiation Mitigators - Greenberger, Joel S.; Clump, David; Kagan, Valerian; Bayir, Hulya; Lazo, John S.; Wipf, Peter; Li, Song; Gao, Xiang; Epperly, Michael W. (Frontiers in Oncology, 2012)
Mitochondrial targeted radiation damage protectors (delivered prior to irradiation) and mitigators (delivered after irradiation, but before the appearance of symptoms associated with radiation syndrome) have been a recent focus in drug discovery for 1) normal tissue radiation protection during fractionated radiotherapy, and 2) radiation terrorism counter measures. Several categories of such molecules have been discovered: nitroxide-linked hybrid molecules, including GS-nitroxide, GS-nitric oxide synthase inhibitors, p53/mdm2/mdm4 inhibitors, and pharmaceutical agents including inhibitors of the phosphoinositide-3-kinase pathway and the anti-seizure medicine, carbamazepine. Evaluation of potential new irradiation dose modifying molecules to protect normal tissue includes: clonagenic radiation survival curves; assays for apoptosis and DNA repair, and irradiation-induced depletion of antioxidant stores. Studies of organ specific radioprotection and in total body irradiation-induced hematopoietic syndrome in the mouse model for protection/mitigation facilitate rational means by which to move candidate small molecule drugs along the drug discovery pipeline into clinical development.